Synthesis of Novel Charged Ice Recrystallization Inhibitors - Charlton, Thomas Aurelio (Université d'Ottawa / University of Ottawa, 2021)
With emerging trends of new cellular therapies, the need for quick access to cellular components is necessary. For most applications genetically compatible biological components are essential to prevent adverse immune responses and graft-versus host disease (GVHD). Since these biological components have a limited window to be used, techniques for long-term storage are needed. Cryopreservation is essential for this in the field of biobanking and regenerative medicine to allow for long-term storage of cell products. During this process, ice recrystallization is the major contributor to cell death and decreased cell viability post-thaw. Due to this, controlling ice growth and recrystallization is imperative to increasing cell survival and function. The Ben lab is focused on the synthesis of small molecule, carbohydrate-based cryoprotectants that function as ice recrystallization inhibitors (IRIs). Previously, many IRIs have been synthesized showing varying degrees of ice recrystallization inhibition (IRI). Through the structure-function work, a delicate balance between hydrophobic and hydrophilic portions on the same molecule must be met. These compounds are believed to disrupt hydrogen bonding networks present in the formation of ice, and control ice growth. While numerous types of functional groups on carbohydrate derivatives have been explored, many highly solvated functional groups (amines, sulfates, phosphates, etc.) have not been thoroughly investigated. Highly solvated functional groups should disrupt hydrogen bond networks due to their solvation and in theory, should illicit an IRI response. Sulfate groups have not previously been studied, but are present in several different biological processes, such as immune response and blood coagulation. This suggests that sulfated carbohydrates should be well tolerated biologically. Sulfate groups can also be easily installed on existing IRI active molecules through orthogonal protecting group chemistry. The first part of this thesis is focused on the synthesis and IRI activity of sulfated carbohydrates based upon previously synthesized, IRI active pyranose derivatives. When compared to their parent compounds, most of the sulfated derivatives were less active, but all compounds were incredibly soluble in aqueous media. These derivatives did not show much promise as new IRIs due to the length of their synthesis and reduced IRI activity compared to their parent compounds. The Ben lab has also developed a new class of IRI active carbohydrates: aldonamide derivatives. These compounds are open-chain carbohydrates with an amide bond, arising from the ring opening of a carbohydrate lactone with a substituted amine. While many of these compounds displayed high degrees of IRI activity, many were incredibly insoluble in aqueous systems (many with solubility limits under 50 mM). Since sulfate groups were able to greatly increase solubility with some derivatives retaining IRI activity, installing sulfate groups on existing aldonamide-based IRIs should increase their solubility. Additionally, since many of these derivatives display high degrees of IRI activity, a reduction in IRI activity can be tolerated. Similarly, to the sulfated pyranose derivatives, the presence of a sulfate group reduced the IRI activity compared to the parent compounds in most derivatives. Though some sulfated derivatives possessed a higher degree of IRI activity, all the derivatives experienced a drastic increase in solubility (over 200 mM in PBS). Some of the sulfated aldonamide derivatives were assessed for their ability to protect red blood cells (RBCs) during freezing with reduced glycerol concentrations (15% glycerol), although none of thew tested derivatives showed an improvement over existing IRIs explored by the Ben lab. Since the introduction of sulfate groups to existing IRIs drastically increased solubility in aqueous systems, but resulted in reduced IRI activity in most compounds, focus was switched to the addition of different hydrophilic functional groups. Amino functional groups were briefly explored with galactose-based pyranose IRIs, aldonamide derivatives had not been explored. Amino groups are present on many biological carbohydrates and should be well tolerated biologically. The addition of amino groups to aldonamide derivatives should increase solubility, with the amino derivatives ideally retaining some IRI activity. The amino aldonamide derivatives synthesized had high solubilities (>500 mM in PBS), but did possess lower degrees of IRI activity. Due to the high solubility these derivatives were initially assessed in the cryopreservation of RBCs with reduced glycerol concentrations. Initial experiments showed improvements over current IRIs, and the compounds were assessed in a number of other biological cryopreservation scenarios including articular cartilage, platelets, and hematopoietic stem/progenitor cells (HSPCs). While the compounds showed toxicity in these cell types, more studies need to be conducted for the cryopreservation of RBCs.
Keywords: Carbohydrate Synthesis; Cryobiology; Cryopreservation; Ice Recrystallization Inhibitors